Mechanism of Histone Deacetylase Inhibitors for Treatment of Idiopathic Pulmonary Fibrosis - ZHOU Jia; LI Long; LIAO Jing (Xiehe Yixue Zazhi)
Idiopathic pulmonary fibrosis(IPF) is a chronic, progressive, and fibrotic interstitial lung disease. In recent years, with the in-depth study of the pathological mechanism of IPF, more and more drug treatment targets for IPF have been discovered. Studies have shown that the dysregulation of epigenetic modifications can induce the occurrence of various lung diseases such as chronic obstructive pulmonary disease, asthma, and IPF. Histone deacetylase(HDAC) is not only a key link in the epigenetic modification process but also a key mediator in the pathogenesis of IPF. HDAC is highly expressed in myofibroblasts and alveolar epithelial cells and can play an important role in the pathogenesis of IPF by regulating the heritable expression of genes related to lung inflammation, fibrosis, and apoptosis. This review elaborates on the potential mechanisms of HDAC inhibitors in IPF from aspects such as epithelial-mesenchymal transition, chronic pulmonary inflammatory response, apoptosis, and macrophage polarization, aiming to evaluate the possibility of HDAC inhibitors as targeted therapeutic drugs for IPF and provide certain reference for related research.